2009
DOI: 10.1002/maco.200905348
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion behaviour of Mg–Al alloys with Al–11Si thermal spray coatings

Abstract: The corrosion resistance of AZ31, AZ80 and AZ91D Mg-Al alloys with Al-11Si thermal spray coatings was evaluated by electrochemical and gravimetric measurements in 3.5 wt% NaCl solution. The changes in the morphology and corrosion behaviour of the Al-11Si coatings induced by a cold-pressing post-treatment under 32 MPa were also examined. The as-sprayed Al-11Si coatings revealed high degree of porosity and poor corrosion protection, which resulted in galvanic acceleration of the corrosion of the magnesium substr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The peaks obtained from XRD analyzes were entirely compatible with the literature. [7,8,18,19] Scanning electron microscope (SEM) images taken at different magnifications of the surface morphologies of AZ31, AZ61, and AZ91 magnesium alloys coated with aluminum by the electric arc spray method are given in Figure 4.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The peaks obtained from XRD analyzes were entirely compatible with the literature. [7,8,18,19] Scanning electron microscope (SEM) images taken at different magnifications of the surface morphologies of AZ31, AZ61, and AZ91 magnesium alloys coated with aluminum by the electric arc spray method are given in Figure 4.…”
Section: Resultsmentioning
confidence: 99%
“…They stated that the coating process improved corrosion resistance due to their work. Pardo et al [ 8 ] AZ31, AZ80, and AZ91D coated magnesium alloys using the thermal spray coating method and examined the corrosion resistance of the coating using electrochemical and weight loss techniques in 3.5 wt.% NaCl solution. They applied a cold‐pressing process under 32 MPa pressure as the finishing process for aluminum coating.…”
Section: Introductionmentioning
confidence: 99%
“…Magnesium alloys are the lightest engineering materials [1], which have promising applications in aerospace, military defense, biomedicine, transportation and the 3C industry [2][3][4][5][6][7][8][9][10] due to their excellent properties such as low density, high mechanical strength, high thermal conductivity and good electromagnetic compatibility [11]. Unfortunately, the poor corrosion resistance of magnesium alloys is still the biggest challenge of expanding their application range [12]. Surface treatment technology is an effective means to improve the corrosion resistance of magnesium alloys.…”
Section: Introductionmentioning
confidence: 99%
“…This combination could provide materials with lower weight than Al-Si/SiCp composites and higher wear and corrosion resistance than bare magnesium alloys. Studies with unreinforced spray coatings have already revealed the improved mechanical and corrosion properties of magnesium alloys coated with Al-based coatings, especially when appropriate posttreatments are applied (Ref [8][9][10][11][12][13][14][15][16][17]; however, the number of studies concerning the corrosion behavior of composite coatings on magnesium alloys is too small (Ref 18-23).…”
Section: Introductionmentioning
confidence: 99%